Peranan Pengendalian Internal dalam Menunjang Efektivitas Sistem Pemberian Kredit Usaha Kecil dan Menengah (Studi kasus di Koperasi Pegawai BRI Cabang Kediri) (Jurnal Manajemen dan Kewirausahaan, 2011)
The objective of this research is to find out the role of internal controls to support the effectiveness of microand middle economic unit credit system in BRI Employees cooperation in Kediri branch. The research design used in this study is case study. The finding of the research showes that the internal control has been effectively implemented. It can be seen from the result of questionnaire which illustrates that 93,75% respondents agree with the effectiveness of internal control. Then, 92,72% respondents agree that credit system is an effective system, Moreover, the role of internal control that supportes the credit system is shown to be effective. 93,65% respondents agree about the effective role of internal control.